An experimental and theoretical study of the erosion of semi-crystalline polymers and the subsequent generation of microparticles. Issue 41 (24th September 2019) - Gaillard, Thibaut; George, Matthieu; Gastaldi, Emmanuelle; Nallet, Frédéric; Fabre, Pascale
Abstract : Degradation of a semi-crystalline polymer, via an enzymatic erosion experiment, evidences microstructure dependent surface patterns and microparticles release. A generic geometric model accounts for the mass loss and predicts a critical release size. Abstract : The increase of plastics and microplastics in the environment is a major environmental challenge. Still, little is known about the degradation kinetics of macroplastics into smaller particles, under the joint actions of micro-organisms and physico-chemical factors, like UV or mechanical constraints. In order to gain insight into (bio)-degradation in various media, we perform accelerated erosion experiments by using a well-known enzymatic system. We show that the microstructure of semi-crystalline polymers plays a crucial role in the pattern formation at their surface. For the first time, the release of fragments of micrometric size is evidenced, through a mechanism that does not involve fracture propagation. A geometric erosion model allows a quantitative understanding of erosion rates and surface patterns, and provides a critical heterogeneity size, parting two types of behavior: spherulites either released, or eroded in situ . This new geometric approach could constitute a useful tool to predict the erosion kinetics and micro-particle generation in various media.